Avaliação de riscos ambientais da estocagem de sal marinho em pilhas - Silva, Ana Carolina Vieira da (Universidade Federal Rural do Semi-Árido, 2019)
Sea salt is considered a product of great importance for the national economy, and most of its production is concentrated in the Costa Branca (RN) region - composed of the municipalities of Areia Branca, Mossoró, Grossos, Macau, Galinhos and Guamaré. Within this context, the objective was to emphasize the environmental impacts caused by the storage of salt in piles. To this end, we analyzed the levels of risks of environmental impacts caused by the salt flats (Failure Analysis Method) and which production stages have the highest degree of impact. It was possible to understand that the impacts caused by salt sliding in the salt piles happen most aggravating in three of the seven stages of its production process and end up being the part of the project that causes the greatest risks. Thus, it is recommended that measures consistent with what is proposed by the Federal Public Prosecutor and CONAMA, as well as appropriate to the peculiarities of each saline, so that it is possible to control the main risks and environmental damage caused by it. In the case studied, it was also perceived the need to create a Solid Waste Management Program to ensure the reduction of waste production, another point that should be highlighted is the suitability of the program to the reality of each saline. However, all must prepare the soil from topographic survey to compaction, as well as ensure that the angle of the stacks is adequate avoiding future environmental hazards.
Artigo
Keywords: Impactos ambientais; Controle Ambiental; Salinas; Environmental impacts; Environmental control; Salines; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA